Mujeres en el origen de la aristocracia ibera: una lectura desde la muerte - Rísquez Cuenca, Carmen; García Luque, Mª Antonia (Complutum, 2007)
This paper examines the relationship between the funeral spaces and the aristocratic society and it studies the roll played by the women in the origin and consolidation of this aristocratic model.